ChatGPT as a Cognitive Tool in Sociology: Students’ Perceptions and Its Impact on Academic Writing Practices - Agung Rinaldy Malik (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study examines how undergraduate sociology students perceive and use ChatGPT as a cognitive tool in their academic writing, focusing on its influence on reasoning, writing strategies, and ethical judgment. Using a qualitative case study design, data were collected from 18 sociology students through in-depth semi-structured interviews and comparative analysis of writing samples produced with and without ChatGPT. Thematic analysis generated three key findings. First, students described ChatGPT as cognitive scaffolding that helped them clarify abstract sociological concepts, generate ideas, and articulate theoretical explanations more coherently. Many viewed the tool as a “thinking companion” that reduced conceptual barriers when engaging with complex theories. Second, ChatGPT contributed to shifts in writing strategies, with students moving from unstructured drafting to more systematic practices such as outlining, coherence checking, and iterative refinement. These changes were evident in writing samples, which demonstrated clearer argumentation and improved organization after AI-assisted drafting. Third, students negotiated a tension between assistance and dependence. While recognizing the tool’s benefits, they expressed concerns about losing their academic voice, weakening critical thinking, or relying too heavily on AI-generated structures. Consequently, they adopted selective strategies, including verifying theoretical content and revising AI-generated text. ChatGPT emerged as a supplementary cognitive partner rather than a replacement for sociological reasoning. The findings underscore the need to integrate AI literacy into sociology curricula to promote critical and ethical AI use in academic writing.